2005
DOI: 10.1590/s1415-47572005000200020
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose synthase molecular marker associated with sugar content in elite sugarcane progeny

Abstract: We describe the development and application of an expressed sequence tag (EST)-derived restriction fragment length polymorphism (RFLP) marker for sugarcane elite genotypes which can be used for quantitative trait loci (QTL) tagging for sugar content. EST-derived RFLP markers for proteins involved in sucrose metabolism have been used in Southern analysis for mapping and gene tagging in elite sugarcane clones. A single dose marker, obtained from a sucrose synthase EST associated with sugar content at the α = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 15 publications
(13 reference statements)
1
29
0
2
Order By: Relevance
“…Sugarcane cultivars have a complex, aneuploid and polyploid genome, which contains 100-120 chromosomes (D'Hont et al, 1996). Due to the complex nature of the genome, molecular analysis of sugarcane is not an easy task; however, different molecular techniques have been employed in sugarcane breeding and trait-related marker studies, including random amplified polymorphic DNA (RAPD) for genetic diversity (Harvey and Botha, 1996;Nair et al, 2002;Pan et al, 2003a), amplified fragment length polymorphism (AFLP) for genome mapping and QTL analysis of yield components (Hoarau et al, 2002;Lima et al, 2002), and restriction fragment length polymorphism (RFLP) in genetic diversity and genome complexity (Lu et al, 1994;Jannoo et al, 1999;Silva and Bressiani, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Sugarcane cultivars have a complex, aneuploid and polyploid genome, which contains 100-120 chromosomes (D'Hont et al, 1996). Due to the complex nature of the genome, molecular analysis of sugarcane is not an easy task; however, different molecular techniques have been employed in sugarcane breeding and trait-related marker studies, including random amplified polymorphic DNA (RAPD) for genetic diversity (Harvey and Botha, 1996;Nair et al, 2002;Pan et al, 2003a), amplified fragment length polymorphism (AFLP) for genome mapping and QTL analysis of yield components (Hoarau et al, 2002;Lima et al, 2002), and restriction fragment length polymorphism (RFLP) in genetic diversity and genome complexity (Lu et al, 1994;Jannoo et al, 1999;Silva and Bressiani, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons between QTL mapping results from different sugarcane studies are difficult due to differences in parental variety, experimental design and the environment, among other factors. However, several studies have reported the detection of a low number of QTLs associated with cane yield and sugar yield traits because all of the genetic maps in sugarcane use only single-dose markers and are not yet saturated (Sills et al 1995;Ming et al 2002a, b;Jordan et al 2004;da Silva and Bressiani 2005;Aitken et al 2006;Piperidis et al 2008). By including additional markers as cofactors in the mapping model, the variation associated with QTLs located outside the mapping interval and the detection of false-positive QTLs were both reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The first QTL mapping study in sugarcane was performed by Sills et al (1995). Other works studies making important contributions to QTL mapping include Ming et al (2001Ming et al ( , 2002a, Hoarau et al (2002), McIntyre et al (2005), da Silva and Bressiani (2005), Reffay et al (2005), Aitken et al (2006Aitken et al ( , 2008, Piperidis et al (2008), Pastina et al (2012), and Shing et al (2013). Specifically, Pastina et al (2012) proposed a mixed model for QTL mapping in sugarcane in order to include complex G 9 E interactions.…”
Section: Introductionmentioning
confidence: 99%
“…SNPs in sugarcane ESTs occurring, on average, once every 122 base pairs in the coding regions were reported (Cordeiro et al 2006). Additionally, RFLP markers based on sugarcane EST have been developed to target sugar content, disease resistance, fiber accumulation, and yield (da Silva et al 2001;Rossi et al 2003;da Silva & Bressiani 2005;Pinto et al 2010).…”
Section: Est Resourcesmentioning
confidence: 99%